Blended Learning to Improve Vocational Life Skills in Making Batik for Disabilities - Wiwik Widajati; Siti Mahmudah; Devina Rahmadiani Kamaruddin Nur; Diah Ekasari; Ni Made Marlin Minarsih; Diah Anggraeny; Danis Ade Dwirisnanda (Jurnal Pedagogi dan Pembelajaran, 2023)
The learning strategies applied by educators are still conventional, including learning vocational skills. This research aims to examine the effect of blended learning on improving the vocational life skills of students with disabilities. This research is pre-experimental. This research design is a group pre-test-post-test design. The research subjects were students with disabilities at the Special High School (SMLAB). Data collection uses performance tests. Data analysis used the Wilcoxon signed-rank test (matched pairs test). The research results show that the vocational life skills of students with disabilities after learning with blended learning have improved more than before learning with blended learning. Learning with blended learning has a better and more positive influence on the vocational life skills of students with disabilities. This research implies that blended learning can improve students' abilities, increasing learning outcomes. In the learning process, students are more active, constructive, communicative, able to follow technological developments, and participate to improve their divergent thinking skills and abilities, in this case, thinking abilities related to vocational skills.